PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS, COLLATERALIZABLE ASSETS, DAN GROWTH IN NET ASSETS TERHADAP KEBIJAKAN DIVIDEN DENGAN FIRM SIZE, FIRM AGE, DAN BOARD SIZE SEBAGAI VARIABEL KONTROL (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2017-2019) - Hariyanti, Nunik; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2021)
ABSTRACT The purpose of this research is to analyze the factors affecting dividend policy. This research using profitability, leverage, liquidity, collateralizable assets, and growth in net assets as a independent variable, and then dividend policy as a dependent variable. In addition, firm size, firm age, and board size are used as a control variable. This research using secondary data and the population of this research is 363 manufacturing firms listed on Indonesian Stock Exchange in period 2017-2019. By purposive sampling method, 44 manufacturing firm were obtained as the sample of this research. The analytical method used in this research is multiple linear regression analysis. The result of this research indicate that profitability and collateralizable assets has a positive and significant effect on dividend policy, leverage have insignificant effect on dividend policy, liquidity has a positive and insignificant effect on dividend policy, and growth in net assets has a negative and significant effect on dividend policy.